Pemanfaatan Kulit Jambu Kristal dan Daun Ubi Jalar sebagai Pupuk Cair dengan Cara Polinasi untuk Meningkatkan Produksi Jambu Kristal - Akhmad Endang Zainal Hasan; Ulya Utami (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Cikarawang Village is one of the villages located around the IPB Campus, Dramaga District, Bogor Regency, West Java Province. Based on the potential of existing resources in the Village Cikarawang, there are important commodities to meet the need of life for the surrounding community. Agriculture in Cikarawang Village is dominated by cassava, sweet potato and guava plants. Waste management of crystal guava and sweet potato leaves has not been utilized optimally. This community service aims to utilize the abundant local potential in the manufacture of liquid fertilizer by pollination to increase the production of guava. The method used was counseling and demonstration of liquid fertilizer. The activity was carried out in Cikarawang Village, Dramaga District, Bogor Regency. Participants numbered 17 people consisting of village heads, chairmen of farmers and farmers. The activity was carried out with two sessions, namely the delivery of material and the practice of making liquid fertilizer. This community service activity from an economic perspective can increase farmers' income by maximizing production.